Хэлний бодлого төлөвлөлтийн асуудал ба монгол хэлний хөгжил: Some aspect of language planning and mongolian language development - O., Myagmarsuren (Mongolian Journal of Foreign Languages and Cultures, 2023)
Purpose of the article deals with the role of language development and language planning with terminology work. One way of developing a language is to understand subtleties of developed languages. To measure language development some criteria are suggested: terminologization, increasing of precision, standardization, reducing of loan-words and increasing of scientific concepts in native language. We need terminology standardization to express individual terms in single definitions and understandings of concepts throughout the world. But in most of our professional fields, there is no standard of term translated and interpreted. In large-scale scientific literature translation in which many people are involved, inconsistency in the translation of the same terminology is inevitable. This paper carried out a comprehensive analysis to terminology definition inconsistency, finding that most are terminology with same meaning but different concepts and definition.